What should pulmonary rehabilitation look like for people living with post-tuberculosis lung disease in the Bishkek and Chui region of the Kyrgyz Republic? A qualitative exploration. Issue 2 (4th February 2022) - Mademilov, Maamed; Mirzalieva, Gulzada; Yusuf, Zainab K; Orme, Mark W; Bourne, Claire; Akylbekov, Azamat; Jones, Amy V; Miah, Ruhme B; Jones, Rupert; Barton, Andy; Malcolm, Dominic; Sooronbaev, Talant; et al.
Abstract : Objective: After experiencing tuberculosis (TB), many people develop post-tuberculosis lung disease (PTBLD). Pulmonary rehabilitation (PR) centrally comprising of education and exercise is recommended internationally for people living with chronic respiratory diseases. However, no such service exists in Kyrgyzstan. This study investigated the opinions of healthcare professionals who would be expected to be potential future referrers to PR and adults living with PTBLD about what a PR programme could look like in Kyrgyzstan. Design: A qualitative study using interviews and focus groups. Grounded theory and thematic analysis were used for data collection and analysis. Participants: 63 participants; 15 referrers (12 male, 3 female; 12 pulmonolgists, 3 TB specialists) and 48 adults (26 male, 22 female) living with PTBLD. Setting: Participants were recruited from hospital settings in Bishkek and Chuy Region, Kygryzstan. Methods: Fifteen semistructured interviews were conducted with referrers and nine focus group discussions were conducted with adults living with PTBLD. Results: Five key themes were developed: (1) living with PTBLD; (2) attitude to PR, which emphasised the perceived importance and potential benefits of implemention; (3) barriers/facilitators to PR, which included time and cost, and the importance of appropriate communication in enabling participation; (4) interventional components of PR, which described culturally and demographically appropriate physical activities including rhythmic movements, dance and volleyball; and (5) psychosocial support, which demonstrated the importance of psychological support for patients coping with the effects of stigma. Conclusions: Potential referrers and adults living with PTBLD expressed their support for the implementation of PR. The culture-specific and population-specific issues highlighted in this work demonstrate the need to address stigma and provide certain types of exercise training/education modules for this specific clinical population. In other respects the currently known attitudes/barriers to PR, identified in Western research, appear to apply. The principles of culturally adapting PR may be helpful for those looking to establish similar clinical services in other low-income and middle-income countries and in Central Asia in particular. Trial registration number: ISRCTN11122503 .